Effects of four weeks of β-alanine supplementation on repeated sprint ability in water polo players - Brisola, Gabriel Motta Pinheiro [UNESP]; Artioli, Guilherme Giannini; Papoti, Marcelo; Zagatto, Alessandro Moura [UNESP] (Public Library of Science (PLoS), 2016)
The purpose of this study was to investigate the effect of four weeks of β-alanine supplementation on repeated sprint ability in water polo players. Twenty-two male water polo players participated in the study, divided randomly into two homogeneous groups (placebo and β-alanine groups). The study design was double-blind, parallel and placebo controlled. Before and after the supplementation period (28 days), the athletes performed two specific repeated sprint ability tests interspaced by a 30-minute swimming test. Participants received 4.8g·day-1 of the supplement (dextrose or β-alanine) on the first 10 days and 6.4g·day-1 on the final 18 days. There was no significant group-time interaction for any variable. The qualitative inference for substantial changes demonstrated a likely beneficial effect in the β-alanine group (β-alanine vs placebo) for mean time (6.6±0.4s vs 6.7±0.4s; 81% likely beneficial), worst time (6.9±0.5s vs 7.1±0.5s; 78% likely beneficial) and total time (39.3±2.5s vs 40.4±2.5s; 81% likely beneficial) in the first repeated sprint ability set and for worst time (7.2±0.6s vs 7.5±0.6s; 57% possible beneficial) in the second repeated sprint ability set. Further, was found substantial change for total time for both repeated sprint ability tests (80.8 ±5.7s vs 83.4±5.6s; 52% possible beneficial). To conclude, four weeks of β-alanine supplementation had a likely beneficial effect in the first set of repeated sprint ability tests and a possible beneficial effect for worst time in the second set performed in a specific protocol in water polo players.